PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS II SD NEGERI 136 PEKANBARU - Alpusari, Mahmud; Antosa, Zariul; ', Widiyawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted with the aim of improving PKn learning outcomes by implementing the role playing learning model for second grade students of SD Negeri 136 Pekanbaru. The low yield was due to the students’ learning during the teacher teaches rely on the lecture method. The learning model resulted in a lack of interest and motivation of students in PKn subjects, because the learning process is dominated by teachers and low student involvement in learning. This study was conducted in 136 SDN Pekanbaru in the second semester of the academic year 2014 / 2015. This classroom action research was conducted in SDN 136 Pekanbaru. As the subject of this research were students of class II SDN 136 Pekanbaru of students 41 consisting of 24 men and 17 women. This research was conducted in two cycles consisting of planning, action, observation, and reflection. The data analysis techniques implemented are the activities of teachers, students’ activity based on observation sheets, and student learning outcomes based on the UH each cycle. Result of learning using role playing learning models have increased from a base score to the first cycle and into the second cycle, in which the first cycle in the classical completeness obtained for 75.6% and in the second cycle increased to 95.1%. Improved learning outcomes obtained in the first cycle was 18.5% and the cycle II of 23.9%. Increased student learning outcomes are influenced by the activities of teachers and students in the learning process is getting better. In the first cycle of activity the teacher and student activity first meeting acquire enough categories, while the second meeting increased the very good categories. Furthermore, on the second cycle of activity of teachers and students’ activity is increasing so it got very good category. The conclusion of this research is the application of role playing learning model can improve student PKn learning outcomes of class II SDN 136 Pekanbaru on the material deliberations.Keywords: Role Playing Learning Model, PKn Learning Outcomes